Kinship, Entrepreneurship and Social Capital: Alcohol Pachters and the Making of Free-Burgher Society in Cape Town, 1652-1795 - Groenewald, Gerald Jacobus (Department of Historical Studies, 2014)
In 1657 the Dutch East India Company (VOC) released fourteen employees from its service who settled as free burghers at the Cape of Good Hope. By 1795 their number had grown to almost fifteen thousand. The original free burghers shared the same sociocultural background and were uniformly poor. Yet in the course of the eighteenth century they developed into a stratified society with a clearly identifiable elite. Hitherto this development had been ascribed to capital accumulation in the form of land and slaves, with a focus on the settled arable farmers. This thesis challenges these arguments by applying the theoretical concept of entrepreneurship to the history of the 198 individuals who served as alcohol pachters (lease holders) in Cape Town between 1680 and 1795. The thesis argues that a study of their economic and social activities leads to greater conceptual clarity and a better understanding of the way in which social mobility operated. This study reveals how intertwined economic success was with social factors; and traces the changing uses and functions of kinship and social capital in VOC Cape Town. It demonstrates the importance of the urban free burghers to the Cape economy and the ways in which this group was linked to the rural free burghers. The first chapter treats the origins and operation of the alcohol pacht (lease) system and its contribution to the Cape economy. This is followed by a prosopographical analysis of all 198 of the alcohol pachters. Chapter three presents the biography of Hendrik Oostwald Eksteen as a vehicle with which to present the theoretical concepts attended on entrepreneurship, which are employed in the rest of the thesis. Chapter four illustrates the importance of social capital and kinship to what was still a largely immigrant society in the 1730s, while chapter five traces the changes which had occurred by the 1770s. These two chapters also demonstrate the ways in which the urban and rural elites coalesced over time. The final chapter shows to what extent the economic success of pachters was translated into other forms of power.